Special Assistance Teachers Learning Strategies for Slow Learner Students in Inclusive Elementary Schools - Akhmad Mukhlis; Bella Kirana Nur Havida; Afif Auliya Nurani (Universitas Negeri Padang, 2023)
This study examines the learning strategies of Special Assistance Teachers (GPK) for students with slow learner barriers of inclusive elementary school age. A qualitative case study approach is used to answer research questions. Sumbersari 1 public elementary school in Malang City was chosen as the research location for two main reasons, namely as the official inclusion primary school for the education office and at the same time as the oldest inclusive primary school and as a reference in Malang City. Six students with slow learner barriers and one special accompanying teacher became research participants for three months. The results showed that the learning strategies used were visual media, drill methods, remedial, teaching everyday life, and approaching slow-learning children with special needs through intense communication. The inhibiting factors of this strategy are learning that requires high reasoning, making slow learners with special needs often feel difficult, low self-confidence, insufficient number of GPK, and less cooperative parents. The supporting factors for this strategy are adequate facilities, appropriate methods, and smooth communication between slow learners, special assistance teachers, and children with special needs.